Comparative Analysis of Modern Directions and Tendencies of European and Chinese Semiotic Research - Максим Кривоніс (Київський національний університет імені Тараса Шевченка, 2025)
Background. The article investigates the directions and tendencies of modern semiotic research conducted by European and Chinese scientists to identify prospects for further semiotic research. The author made a brief historical analysis and highlighted modern tendencies in English and Chinese semiotic research as well as topical directions and trends in European and Chinese semiology and outlined the perspectives of semiotic research. Special attention is paid to the leading scientists of the semiotic field and the spheres of their scientific interests. Methods. In preparing this publication, a descriptive method was used to analyze directions and tendencies. The contrastive explanatory approach was used to single out the standard and distinctive features in the semiotic studies of Europe and China. While comparing the views of scientists, the author outlined modern perspective directions in the field of semiotics. Results. Therefore, after conducting a comparative analysis, the author demonstrated distinctive ethnosemiotic and biosemiotic interests of the researchers in Chinese-language semiotic scientific discourse; common directions of Chinese and European semiotic research include digital semiotics, narrative structures of sense-making and iconicity in social networks, research on reputational discourse, and issues of ecosemiotics. The scientific interests of leading Western and Chinese semiologists were compared with those of Ukrainian researchers, outlining common and distinct research areas. Conclusions. The research has proven the topicality of conducting the ethnosemiotic and linguosemiotic research in the field of interdisciplinary semiotic systems, the study of Chinese and European, in particular Ukrainian linguistic culture, religious studies, works of visual art, verbal and non-verbal iconic signs, and the semiotics of literary and artistic discourses. It may be considered a perspective to conduct the studies of the semiotic features of post-digital education, localization, law, the global influence of social networks, and the study of the functioning of iconic units in diachrony, in particular, in the integration of diachronic and synchronic typology perspectives, supplemented by cognitive-linguistic and cultural aspects.

Вступ. Дослідження ставить на меті аналіз напрямів і тенденцій передових семіотичних досліджень нау-ковцями Європи та Китаю для виявлення перспектив проведення подальших порівняльних розвідок вітчизня-ними дослідниками в цій царині. Автором здійснено короткий історичний аналіз і виділено тематичну специфіку галузевої складової англо-мовних та китайськомовних семіотичних досліджень; виділено популярні напрями й тенденції сучасних євро-пейських і китайських семіотичних досліджень; окреслена перспектива вітчизняних компаративних семіотич-них досліджень. Виділені сфери наукових інтересів провідних науковців семіотичної галузі. Методи. Для аналізу напрямів і тенденцій застосовано описовий метод наукового дослідження. За допо-могою використання прийому зіставної інтерпретації виокремлено спільні та відмінні риси у семіотичних дос-лідженнях Європи та Китаю. Насамкінець, за допомогою методу зіставлення поглядів науковців було окреслено сучасні перспективні напрями семіотичних досліджень. Результати. Відтак, після проведення зіставного аналізу, автором продемонстровано виразну етносе-міотичну тематику й біосеміотичну направленість досліджень китайськомовного семіотичного наукового дис-курсу; до спільних напрямів китайських і європейських семіотичних досліджень можна віднести питання циф-рової семіотики, питання наративних структур сенсоутворення та іконічності в соціальних мережах, дослі-дження репутаційного дискурсу, проблем екосеміотики. Автором схарактеризована сфера наукових інтересів провідних західних семіологів і семіологів із КНР, проведені паралелі з українськими дослідниками. Висновки. Унаслідок проведеної наукової розвідки доведено перспективність здійснення етносеміотич-них і лінгвосеміотичних досліджень у галузі використання інтердисциплінарних семіотичних систем, дослі-дження китайської та європейської, зокрема української, лінгвокультур, релігієзнавства, творів візуального мистецтва, вербальних і невербальних зображувальних знаків, і семіотики літературного й мистецького дис-курсів. Перспективними можуть вважатися дослідження семіотичних особливостей постцифрової освіти, ло-калізації, права та глобального впливу соціальних мереж і дослідження функціонування іконічних одиниць в діах-ронії, зокрема в інтеграції ракурсів діахронічної і синхронічної типології, доповнених когнітивним та лінгвоку-льтурологічним аспектами.
Порівняльна характеристика сучасних напрямів і тенденцій європейських та китайських семіотичних досліджень
Keywords: семіотичне дослідження; символ; Китай; Європа; зіставний аналіз; мультимодальність; semiotic research; symbol; China; Europe; comparative analysis; multimodality